435. A DIAGNOSTIC PITFALL; SMALL CELL CARCINOMA-LIKE FEATURES IN BASALOID SQUAMOUS CELL CARCINOMA OF THE ESOPHAGUS. (24th September 2022) - Ishida, Hirotaka; Kasajima, Atsuko; Yamauchi, Takuro; Kato, Nobufumi; Koseki, Ken; Ozawa, Yohei; Okamoto, Hiroshi; Sato, Chiaki; Taniyama, Yusuke; Fujishima, Fumiyoshi; Kamei, Takashi; Sasano, Hironobu
Abstract: Esophageal basaloid squamous cell carcinoma may resemble small cell carcinoma biopsy specimens and cause difficulties in pathology diagnosis. We aimed to explore the pathological features of basaloid squamous cell carcinomas in biopsy specimens that mimic small cell carcinoma and to clarify their diagnostic and prognostic features. This study will contribute to draw attention to an important pitfall in pathology diagnosis in endoscopic biopsy specimens of the esophagus. Thirty biopsy specimens of esophageal basaloid squamous cell carcinoma were reviewed and compared with 13 matched surgical specimens. A small cell carcinoma-like feature was defined as, when at least one of the three following findings was observed: 1) diffuse growth pattern, 2) nuclear molding and 3) nuclear crush artifact. Immunohistochemistry of synaptophysin, chromogranin A, CD56 (neuroendocrine markers) and p16 were performed in all cases. Small cell carcinoma-like features, such as diffuse growth, nuclear molding, or nuclear crush artifact, were identified in 80% (24/30) of the biopsies and in 77% (10/13) of the surgery specimens, but in a proportionally much smaller area in the surgical specimens than in the biopsy samples. The presence of a small cell carcinoma-like feature had no impact on patients´ outcome. Immunohistochemically, synaptophysin and chromogranin A were consistently negative, while CD56 was expressed in 42% (10/24) basaloid squamous cell carcinomas with small cell carcinoma-like features. p16, a highly sensitive marker for small cell carcinoma, was also expressed in 8% (2/24). In conclusion, small cell carcinoma-like features are frequent and conspicuous in biopsies, which may probably be caused by exogenous factors such as friction and external pressure that occur in biopsy procedure and in the tumor environment. Small cell carcinoma-like features may lead to a misinterpretation of a true small cell carcinoma, if CD56 is an only neuroendocrine marker expressed. p16 expression may be also detected in basaloid squamous cell carcinoma.